Physical activity as a predictor of fremanezumab response in chronic migraine – the Phy-Fre-Mig study - Álvaro Sierra-Mencía; Andrea Recio-García; David García-Azorín; Antonio José Molina de la Torre; Isabel Ros González; Ángel Luis Guerrero-Peral (The Journal of Headache and Pain)
Abstract Background The relationship between physical activity (PA) and migraine is insufficiently understood. Studies have not analysed levels of PA or Time Sitting (TS) during preventive treatment, nor the role these might play in the response to preventive treatment. Methods An observational, longitudinal prospective study in a headache clinic was conducted. All consecutive chronic migraine patients initiating fremanezumab were invited to participate and were followed for three visits. The International Physical Activity Questionnaire (IPAQ) - long version was used. Results Seventy-six patients with a median of 46 years old, 84.2% female were enrolled. One month after fremanezumab administration, there was a significant increase of most PA variables and a significant decrease in TS levels compared with baseline; headache days and walking, TS and migraine days showed a moderate correlation. Three months after initiation, all PA variables statistically increased and TS levels statistically decreased, and variables such as headache/migraine days showed a moderate correlation with all PA variables analysed. In the multivariate analysis, higher levels of walking at baseline were independently associated with response to fremanezumab (ORa: 1.194; CI: 1.018–1.401, p = 0.029). Conclusion Patients who spent more time walking before starting treatment, were more likely to have a response to fremanezumab. PA and TS levels changed since the first month and correlated with clinical variables.